2017
DOI: 10.1002/jor.23711
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hip replacements between 1999 and 2012 in Sweden

Abstract: National Registers document changes in the circumstance, practice, and outcome of surgery with the passage of time. In the context of total hip replacement (THR), registers can help elucidate the relevant factors that affect the clinical outcome. We evaluated the evolution of factors related to patient, surgical procedure, socio‐economy, and various outcome parameters after merging databases of the Swedish Hip Arthroplasty Register, Statistics Sweden and the National Board of Health and Welfare. Data on 193,25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
(58 reference statements)
2
25
0
Order By: Relevance
“…Patients presenting for surgery in more recent years may be healthier, either because patients are generally healthier than in the past, or because the selection criteria have changed over time (not operating on patients at higher risk). However, this explanation is unlikely to be true because other studies have shown that the decrease in early post‐operative mortality has occurred despite a corresponding increase in comorbidities . Explanatory treatment factors may include pre‐operative interventions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients presenting for surgery in more recent years may be healthier, either because patients are generally healthier than in the past, or because the selection criteria have changed over time (not operating on patients at higher risk). However, this explanation is unlikely to be true because other studies have shown that the decrease in early post‐operative mortality has occurred despite a corresponding increase in comorbidities . Explanatory treatment factors may include pre‐operative interventions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using National Joint Registry data from England and Wales, early mortality after hip and knee replacement surgery for osteoarthritis fell by nearly 50% between 2003 and 2011 . A study from Denmark showed a decrease in 30‐day mortality of greater than 50% over a 15‐year period after hip and knee replacement and research from Sweden has shown a significant decrease in 30‐ and 90‐day mortality after hip replacement for osteoarthritis between 1999 and 2012 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Swedish hip fracture register [http:// www.rikshoft.se] started in 1988. The Swedish Hip Arthroplasty Register (SHAR) has been important to identify implants that have not performed well, consequently, they have been removed from the market (Cnudde et al, 2016(Cnudde et al, , 2017. The hip replacement registry allowed researchers to study over time specific hip prostheses, including postmarket surveillance of individual implant performance, surgical procedures, and units were associated with the fewest reoperations (Ovretveit, Nelson & James, 2016).…”
Section: Rikshöft the Swedish Hip Fracture Registermentioning
confidence: 99%